MATHEMATICAL INNOVATION: INNOVATIVE TEACHING PRACTICE OF PROPORTIONALITY - Martins Lopes, Rivanaldo (Journal of Interdisciplinary Debates, 2023)
Introduction: The study of proportionality in high school has been presented as essential content in student learning. In this context, the present work aims to present a new innovative model for solving simple rule of three problems, as a tool in teaching practice in contemporary education. To achieve the objectives proposed in this work, the research was carried out at ECIEM Dorgival Silveira, with a qualitative-quantitative method with 118 high school students in an experimental way, with discrete variable data and data analysis with the aid of descriptive statistics. In the development of this method, the social contribution will be an innovative learning product that will facilitate the difficulties experienced by mathematics students. Thus, this new tool was presented with support for efficiency and effective results, proposing that other researchers seek new research in this field that still needs new innovation regarding the types of materials.